MENGGALAKKAN DEKONSTRUKSI TERHADAP BIBIT-BIBIT TERORISME DI INDONESIA - Fanny Tanuwijaya; Sunardi Sunardi (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2018)
ABSTRACTTerrorism is one of extraordinary crimes. The extraordinary of this crime is not only because it can cause serious impacts on the community life in general, but it also because of its ability to establish regeneration. This terrorist organization is quite successful in recruiting new members. This effectively encourages the willingness and the commitment of their members in conducting serious crimes in relation to terrorists conducts. In this circumstance, it is quite reasonable that all parties are encouraged to respond critically by deconstructing those terrorists’ regenerations.  Keywords: Terrorism, Regeneration, Deconstruction, Society, Nation  ABSTRAKTeroris merupakan salah satu jenis kejahatan isimewa (extraordinary crime). Keistimewaan kejahatan ini bukan semata disebabkan dampaknya yang serius terhadap kehidupan bermasyarakat dan berbangsa, tetapi juga dari sepek kemampuannya dalam membangun regenerasi. Organisasi teroris ini tergolong sukses dalam melakukan pembimbitan kader, sehingga untuk menjalankan modus operandi yang tergolong mengerikan, ada saja kader yang mau melaksanakannya. Berdasarkan kondisi ini, logis jika semua pihak dituntut melakukan dekonstruksi terhadap kaderisasi teroris.Kata Kunci: Terorisme, Kaderisasi,  Dekonstruksi, Masyarakat, Negara.